2015
DOI: 10.1111/sipr.12010
|View full text |Cite
|
Sign up to set email alerts
|

New Routes to Recruiting and Retaining Women in STEM: Policy Implications of a Communal Goal Congruity Perspective

Abstract: Despite advances within a wide range of professional roles, women remain a minority in science, technology, engineering, and mathematics (STEM) degrees and occupations. The gender gap in mathematics and science performance has converged, and so it is important to consider the motivational reasons that might underlie the differential STEM pursuits of women and men. The goal congruity perspective contends that a fundamental cause of gender gaps in STEM pursuits is the gender difference in communal motivation (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 133 publications
7
115
0
9
Order By: Relevance
“…As noted earlier, the bulk of prior research on gender differences in switching majors concentrates on comparing women in STEM fields to men in STEM fields (Diekman et al, 2015; Mann and DiPrete, 2013; Riegle-Crumb et al, 2012; Xie and Shauman, 2003). Yet our study was specifically focused on a related but distinct issue not addressed in this prior literature, namely whether women in male-dominated fields are more likely than their female peers in more normative majors to leave their chosen field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted earlier, the bulk of prior research on gender differences in switching majors concentrates on comparing women in STEM fields to men in STEM fields (Diekman et al, 2015; Mann and DiPrete, 2013; Riegle-Crumb et al, 2012; Xie and Shauman, 2003). Yet our study was specifically focused on a related but distinct issue not addressed in this prior literature, namely whether women in male-dominated fields are more likely than their female peers in more normative majors to leave their chosen field.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly a study of college students at a highly selective university found that exposure to gender/STEM stereotypes decreased women’s sense of belonging in math, which the authors then linked to a lower desire to pursue math in the future (Good et al, 2012). Although the literature on stereotype threat is often experimental, with cues specifically manipulated by researchers, there is ample evidence that women who enter such male-dominated fields are very likely to be exposed to gender stereotypes that decrease their desire to persist (Diekman et al, 2015; Shapiro and Williams, 2012), which could plausibly result in higher switching rates than those of women in other fields.…”
Section: Deterrents To Women’s Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…This difference in values is not innate in women and men, but is hypothesized, using social role theory, to be due to the historical emphasis on women being in more caregiving roles. This has led to the female gender role emphasizing more communal traits (reviewed in Diekman et al [118]). …”
Section: Conflict Between Personal Goals and Stereotypes About The Prmentioning
confidence: 99%
“…Researchers across the disciplines of psychology, sociology, education, and many others offer an assortment of possible explanations for the underrepresentation of women in STEM (Ceci and Williams 2007;Diekman et al 2015). Recent reviews have called for greater emphasis on the role of girls' and women's personal choice in the process of selecting a STEM career (Valla and Ceci 2014), along with an understanding of how these choices are influenced by both individual-level and structural-level factors (Diekman and Fuesting).…”
Section: Introductionmentioning
confidence: 99%